THE ECONOMIC EVALUATION OF RESEARCH-BASED INDONESIAN COAL UTILIZATION - Ukar Wijaya Soelistijo; Suganal Suganal (Puslitbang tekMIRA, 2013)
Efforts of Indonesian Government in diversifying the available fuels from domestic coal in the forms of solid, liquid and gaseous fuels open the pissibility to overcome the depleted domestic oil reserves. Within the coming few years, Indonesia will be a net oil consumer after being the net oil importer in 2003. In the last forty years, Indonesian energy consumption was heavily depended on oil fuel. To meet the increase domestic energy demand, a large quantity of domestic coal reserves should be diversified into briquette, synthetic oil and gas as well as other non-fuel or chemical products. All these diversified products are expected to be economically competitive as well as environmental friendly using clean coal technology. This article is an evaluation on study results compilation of Indonesian coal utilization and diversification in the last 15 years